Role of Primary Care Optometrists in the Assessment and Management of Patients with Traumatic Brain Injuries in Canada - Lacroix, Zoe; Leat, Susan J.; Christian, Lisa W. (Canadian Journal of Optometry, 2018)
Traumatic brain injury (TBI) results from a strong blow or jolt to the head that disrupts the normal function of the brain.1 The severity of a TBI can range from mild to severe, depending on the patient’s mental status, con-sciousness level and amnesia following the injury. The annual incidence of TBI in North America and Europe is conservatively estimated to be ap-proximately 600/100,000.2,3 This translates to at least 200,000 TBI cases in Canada every year. According to the Centers for Disease Control and Prevention, and the Canadian Institute for Health Information, the leading cause of TBIs that result in hospital admission is falls (35%-45%), followed by motor vehicle accidents (17%-36%), collision-related events (struck by or against) (10-17%) and assaults (9-10%).4,5 Head injuries are more common in the 0- to 19-year age group, followed by those who are aged 60+. Males are more highly represented in every age group than females. However, it should be noted that the demographics of patients who present in an op-tometrist’s office may differ from those based on hospital admissions [...]